Pencegahan Patologi Birokrasi Melalui Reformasi Administrasi Pelayan Publik - Nabila Hidayah; Evi Priyanti (Peneliti.net, 2022)
This paper examines the avoidance of bureaucratic disease through the reform of public sector management using the Purwakarta Regency Environmental Service as a case study. This research was conducted to assess the public service administration performance of the Purwakarta Regency Environmental Service workers. This study employs a qualitative methodology. Qualitative research is a kind of inquiry that generates descriptive data in the form of written inner speech and observable behavior from the subjects themselves. By employing a qualitative methodology, it is possible to build and strengthen a theory, as well as collect facts and information linked to the avoidance of bureaucratic disease. This study indicates that the Purwakarta Regency Environmental Service lacks oversight, resulting in public service maladministration, as well as a loss of public confidence, resulting in a decline in public satisfaction with the delivery of public services.